2021
DOI: 10.1111/opo.12814
|View full text |Cite
|
Sign up to set email alerts
|

Ocular biometry in children and adolescents from 4 to 17 years: a cross‐sectional study in central Germany

Abstract: Purpose To evaluate ocular biometry in a large paediatric population as a function of age and sex in children of European descent. Methods Children were examined as part of the LIFE Child Study (Leipzig Research Centre for Civilization Disease), a population‐based study in Leipzig, Germany. Altogether, 1907 children, aged from 4 to 17 years, were examined with the Lenstar LS 900. Data from the right eye was analysed for axial length, central corneal thickness, flat and steep corneal radii, aqueous depth, lens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 52 publications
(150 reference statements)
2
22
3
Order By: Relevance
“…24 Comparing AL to European and other ethnic counterparts, longer AL was observed in Chinese children at all ages; the difference increased with age. [25][26][27][28][29] For example, at 6, 9 and 15 years of age, differences in AL for males from current study to those reported by Tideman et al was…”
Section: Discussioncontrasting
confidence: 47%
“…24 Comparing AL to European and other ethnic counterparts, longer AL was observed in Chinese children at all ages; the difference increased with age. [25][26][27][28][29] For example, at 6, 9 and 15 years of age, differences in AL for males from current study to those reported by Tideman et al was…”
Section: Discussioncontrasting
confidence: 47%
“…In He et al's [ 34 ] research on Shenzhen kindergarten children aged 3–6 years, girls had shorter AL and ACD and higher LP, and the differences were statistically significant. Other local and foreign studies [ 40 , 41 , 42 ] have also reported this association numerous times, but the rationale remains to be elucidated. Considering that LP decreases with age, maybe among the same age, boys grow faster and earlier than girls.…”
Section: Discussionmentioning
confidence: 93%
“…Myopia often progresses in school-age children, and changes in the balance of each ocular component with growth may be related to the progression of myopia [ 6 ]. The sex- and age-specific mean values of the ocular components have been investigated among children in many countries and regions, including Taiwan [ 7 ], Hong Kong [ 8 ], mainland China [ 9 ], and Germany [ 10 ], using school-based cross-sectional designs. However, to the best of our knowledge, no studies have reported sex- and age-specific summary statistics of these various measurements in a general population with a wide age range using a school-based design in Japanese children.…”
Section: Introductionmentioning
confidence: 99%